2016
DOI: 10.1371/journal.pone.0158389
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Peritonitis: Underestimated Disease in Critically Ill Patients with Liver Cirrhosis and Spontaneous Peritonitis

Abstract: IntroductionSpontaneous peritonitis, especially spontaneous fungal peritonitis (SFP), is an important and potentially fatal complication in patients with endstage liver disaese. We evaluated potential risk factors, microbiological findings, and outcome of patients with SFP compared to spontaneous bacterial peritonitis (SBP) in critically ill patients.MethodsRetrospective analyses of critically ill patients with suspected spontaneous peritonitis.ResultsOut of 205 patients, 20 (10%) had SFP, 28 (14%) had SBP, 48… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 16 publications
4
74
1
Order By: Relevance
“…Invasive candidiasis was the dominant (64%) IFI followed by the invasive aspergillosis (36%) in patients with ACLF. Others have reported the similar spectrum of fungal infections in cirrhosis . This is likely because of fungal dysbiosis and breach in gut mucosal barrier in advanced cirrhosis and hence the transmucosal migration of commensal Candida or superinfection because of Aspergillus species …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Invasive candidiasis was the dominant (64%) IFI followed by the invasive aspergillosis (36%) in patients with ACLF. Others have reported the similar spectrum of fungal infections in cirrhosis . This is likely because of fungal dysbiosis and breach in gut mucosal barrier in advanced cirrhosis and hence the transmucosal migration of commensal Candida or superinfection because of Aspergillus species …”
Section: Discussionmentioning
confidence: 81%
“…Recently, Bajaj et al reported IFI in 5% cirrhotics (of which 43% had ACLF). Others have reported a variable occurrence of fungal infections in patients with cirrhosis (1%‐66%) . The variability was because of lack of a uniform diagnostic criteria, confounding because of fungal colonization, delayed diagnosis owing to use of conventional diagnostics only in addition to heterogeneous aetiologies and variable severity of liver dysfunction in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…is the most common fungus isolated [4][5][6]. SFP mortality is very high ranging from 90% to 100% of patients [4,5]. Hospitalization seems to be a SFP risk factor [4,5].…”
Section: Editorialmentioning
confidence: 99%
“…SFP mortality is very high ranging from 90% to 100% of patients [4,5]. Hospitalization seems to be a SFP risk factor [4,5]. In a randomized controlled trial, an antifungal agent was added in hospital-acquired SBP with no response to broad-spectrum antibacterial agents: the results of this study showed that addon of an antifungal agent are more effective than antibacterial alone as empirical antimicrobial treatment of SBP [7].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation